Upaya Meningkatkan Pengetahuan dan Keterampilan Memainkan Instrumen Musik Recorder Melalui Metode Tutorial Sebaya - Sutiyem Sutiyem (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
In learning music, knowledge and skills to play music instruments are very important things. But in reality students of class VII A of SMP Negeri 1 Jetis Bantul are still low in knowledge and skills in playing music recorder instruments. Therefore the author tries to overcome this problem by using the Peer Tutorial method in learning on the material of playing a music recorder instrument. The objectives of this study are: (1) improving knowledge through learning the peer tutorial method on material playing music recorder instruments, (2) improving the ability to play music recorder instruments individually using the peer tutorial method. This research is a classroom action research using two cycles with a total of 32 students. Data collection techniques in this study used student observation, teacher observation, written tests, and practice tests. The results of class action research showed that the completeness of the written test of the first cycle was 71.88% and the second cycle was 90.63%. The results of the completeness of the practical test cycle I were 68.75% and the second cycle was 87.5%. The conclusion of this study is the method of learning peer tutorials can improve the knowledge of music art and skills to play music recorder instruments.